O direito à educação nos centros socioeducativos de internação do Estado do Ceará: um direito condicionado? - Costa, Anna Gabriella Pinto da (2021)
The present work aims to analyze the effective right to education in the socio-educational centers of detention in Fortaleza and its possible limitation or relativization depending on circumstances of time, space, relationships and interactions inherent to the socioeducational system, specifically during the fulfillment of the measure of detention. Initially, it develops the evolution of public policies aimed at young offenders, whose time frame begins with the emergence of specialized laws in the area of childhood and youth, with the Mello Mattos Code of 1927 and the Minors Code of 1979, passing through by the Federal Constitution of 1988 and by the Statute of Children and Adolescents (Law nº 8.069/90) until the implementation of the National Social and Educational Service System (Law nº 12.594/2012). Subsequently, the right to education is presented as a subjective public right and the possible limiting circumstances of this right in socioeducational centers. Therefore, the methodology addressed in the research is bibliographic and normative, with the use and critical disposition of doctrine, normative diplomas and Inspection Reports carried out by the Public Ministry of the State of Ceará and Monitoring Reports of the Public Defender of the State of Ceará in the Socioeducational Centers São Francisco, Patativa do Assaré and Aldaci Barbosa Mota, located in Fortaleza-Ce. A qualitative study is also carried out with discourse analysis of the collective subject, based on essays written by adolescents in conflict with the law in compliance with a detention measure in socio-educational centers in the State of Ceará, allowing the participation of the subjects of these relationships and interactions in the construction of scientific knowledge and theoretical foundations of research. It is concluded that the way educational processes are applied within the socio-educational system relativizes access to education, making it impossible to achieve the emancipation of young offenders, thus representing a system of social reproduction of the subordinate place of these adolescents.